2017
DOI: 10.1002/celc.201700239
|View full text |Cite
|
Sign up to set email alerts
|

3D Ordered Macroporous Carbon Encapsulated ZnO Nanoparticles as a High‐Performance Anode for Lithium‐Ion Batteries

Abstract: A one‐step template‐based technique for the fabrication of three dimensionally ordered macroporous carbon (3DOMC) was developed. 3DOMC, prepared using silica crystal as a template and soluble resol as a carbon source, possesses ordered macropores with mesoporous walls. ZnO nanoparticles were deposited on as‐prepared 3DOMC via a simple in situ growth process to form a ZnO/3DOMC anode material for lithium‐ion batteries. In the composite, the ZnO nanoparticles (≈3.9 nm) were well‐dispersed on the walls of 3DOMC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 41 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…165 Zhang et al prepared a 3D ordered macroporous carbon (3DOMC), which, when prepared with silica crystals as a template, has ordered macropores and mesopore walls. 166 Park et al reported 3D porous microspheres using hollow NiCo 2 O 4 polyhedron (H-NCO/CNT)-modified interconnected carbon nanotubes (CNT) as materials for LIBs. Using a combination of spray pyrolysis and solution methods, a composite with reasonable design was successfully prepared.…”
Section: Mo Nanocompositesmentioning
confidence: 99%
“…165 Zhang et al prepared a 3D ordered macroporous carbon (3DOMC), which, when prepared with silica crystals as a template, has ordered macropores and mesopore walls. 166 Park et al reported 3D porous microspheres using hollow NiCo 2 O 4 polyhedron (H-NCO/CNT)-modified interconnected carbon nanotubes (CNT) as materials for LIBs. Using a combination of spray pyrolysis and solution methods, a composite with reasonable design was successfully prepared.…”
Section: Mo Nanocompositesmentioning
confidence: 99%
“…Utilizing ZnO has several advantages, such as simple synthesis methods, abundant reserves on the Earth, and the fact that it is environmentally friendly [13]. Most importantly, the theoretical specific capacity of ZnO is 978 mAh g −1 , which leads this to be a good potential material for LIBs [14].…”
Section: Introductionmentioning
confidence: 99%